A Review on Homogeneous Charge Compression Ignition and Low Temperature Combustion by Optical Diagnostics - Chao Jin; Zunqing Zheng (Journal of Chemistry)
Optical diagnostics is an effective method to understand the physical and chemical reaction processes in homogeneous charge compression ignition (HCCI) and low temperature combustion (LTC) modes. Based on optical diagnostics, the true process on mixing, combustion, and emissions can be seen directly. In this paper, the mixing process by port-injection and direct-injection are reviewed firstly. Then, the combustion chemical reaction mechanism is reviewed based on chemiluminescence, natural-luminosity, and laser diagnostics. After, the evolution of pollutant emissions measured by different laser diagnostic methods is reviewed and the measured species including NO, soot, UHC, and CO. Finally, a summary and the future directions on HCCI and LTC used optical diagnostics are presented.